Benchmark of Neutronics and Thermal-hydraulics Coupled Simulation program NTC on beam interruptions in XADS. (March 2015) - Wang, Zhen; Wang, Gang; Gu, Zhixing; Jin, Ming; Wu, Yican
Highlights: A Neutronics and Thermal-hydraulics Coupled code is developed for transient analysis. The spatial kinetics model was employed in the benchmark. The simulation correctness of NTC accuracy demonstrated by benchmark. Abstract: The Neutronics and Thermal-hydraulics Coupled Simulation program (NTC) is developed by FDS Team, which is a code used for transient analysis of advanced reactors. To investigate the capacity and calculation correctness of NTC for transient simulation, a benchmark on beam interruptions in an 80 MWth LBE-cooled and MOX-fuelled experimental accelerator-driven sub-critical system XADS was carried out by NTC. The benchmark on beam interruptions used in this paper was developed by the OECD/NEA Working Party on Scientific Issues in Partitioning and Transmutation (WPPT). The calculation model had the minimum phenomenological and computational complexity which concerned a simple model (single fuel channel thermal-hydraulics) of the average fuel pin corresponding to the BOL fuel condition. This benchmark was designed to investigate the temperature and power responses caused by beam interruption of different durations, which aimed at comparative assessment of NTC and other computation methods. A comparison of NTC and other ten sets of temperature and power was provided, which showed that the results had good agreement.